Novel probiotic Lactobacillus helveticus WIS02 alleviates diabetes through multi-pronged regulation of glycolipid metabolism, pancreatic protection and gut microbiota remodeling - Guo, Shuang; Li, Yuying; Yang, Yanan; Jiang, Yuexiao; Wang, Yufeng; Cao, Ying; Duan, Yunfeng; Wu, Chongming (Frontiers in Microbiology, 2026)
BackgroundDiabetes mellitus poses a global health burden with limited therapies derived from breast milk targeting its systemic complications. Probiotics like Lactobacillus helveticus show metabolic benefits, but strain-specific efficacy and mechanisms remain unclear.MethodsThis study evaluated L. helveticus WIS02’s therapeutic potential in streptozotocin (STZ)-induced diabetic mice, focusing on glycemic control, tissue protection, and gut microbiota modulation.ResultsWe found pre-administration of WIS02 for 7 days reduced the final fasting blood glucose by 66.0% and improved oral glucose tolerance (AUC decreased by 51.6%). Additionally, WIS02 significantly mitigated dyslipidemia (TC decreased by 23.6%, TG decreased by 39.5%) and alleviated tissue damage to the liver, pancreatic, and colon tissues. Microbiota analysis revealed that WIS02 treatment significantly altered the gut microbiota structure, increasing the proportion of beneficial bacteria, particularly Akkermansia muciniphila and Parabacteroides distasonis. Correlation analysis between microbiota abundance and physiological indicators showed that Parabacteroides distasonis, Oscillibacter valericigenes, and Akkermansia muciniphila were significantly negatively correlated with blood glucose and lipid levels, while positively correlated with insulin and hepatic glycogen levels.ConclusionL. helveticus WIS02 exhibits multi-targeted efficacy against diabetes by regulating glycolipid metabolism, protecting tissues, and remodeling gut microbiota. These findings highlight its potential as a novel probiotic for metabolic disorder management, warranting clinical translation.